Medication supply to residential aged care facilities in Western Australia using a centralized medication chart to replace prescriptions - Hoti Kreshnik; Hughes Jeffery; Sunderland Bruce (BMC Geriatrics, 2012)
Abstract Background Current model of medication supply to R(RACFs) in Australia is dependent on paper-based prescriptions. This study is aimed at assessing the use of a centralized medication chart as a prescription-less model for supplying medications to RACFs. Methods Two separate focus groups were conducted with general practitioners (GPs) and pharmacists, and another three with registered nurses (RNs) and carers combined. All focus group participants were working with RACFs. Audio-recorded data were compared with field notes, transcribed and imported into NVivo® where it was thematically analyzed. Results A prescription-less medication chart model was supported and it appeared to potentially improve medication supply to RACF residents. Centralization of medication supply, clarification of medication orders and responding in real-time to therapy changes made by GPs were reasons for supporting the medication chart model. Pharmacists preferred an electronic version of this model. All health professionals cautioned against the need for GPs regularly reviewing the medication chart and proposed a time interval of four to six months for this review to occur. Therapy changes during weekends appeared a potential difficulty for RNs and carers whereas pharmacists cautioned about legible writing and claiming of medications dispensed according to a paper-based model. GPs cautioned on the need to monitor the amount of medications dispensed by the pharmacy. Conclusion The current use of paper prescriptions in nursing homes was identified as burdensome. A prescription-less medication chart model was suggested to potentially improve medication supply to RACF residents. An electronic version of this model could address main potential difficulties raised.